Aplicação de TTF em amostras do Terreno Greenstone/TTG de Almas, Tocantins, Brasil - Pereira, Vinicius de Queirós (Universidade Federal de São Carlos, 2022)
The details of the tectonic evolution of the Greenstone/TTG terrains of Almas-TO are still unknown. Until then, there was no thermochronology study (via Fission Track Thermochronology - FTT) on zircon and apatite. Thus, using thermo and geochronological techniques, this work sought to unravel the tectonic processes that occurred after the stabilization of the Almas greenstone, as well as better define its evolution during geological time. This study is of great scientific interest, as it is the most extensive granite-greenstone terrain in the entire Brasilia Belt and economic due to the extensive presence of gold, mainly in the greenstones and diamonds in the sedimentary sequences of the Natividade Group that cover them. Through FTT in zircon it was possible to define the geological processes that occurred at intermediate-low temperature, and, finally: using FTT applied in apatite, we sought to identify the events of denudation, erosion, uplift and subsidence that occurred during the Phanerozoic, especially with reference to to the movements of the Trans-Brazilian Lineament. The results identify the geological events and show the complexity of the evolution of the area: Brasiliana and Gondwanides Orogeny, the breakup of the African and South American plates, and deposition of the Sanfraciscana and Bauru Basins. There are still indications of events in the Andean orogeny.
FTT application on samples on Greenstone/TTG Almas Terrain, Tocantins, Brazil
Keywords: Termocronologia por Traços de Fissão; Geocronologia; Apatita; Zircão; Greenstone/TTG Almas; Fission-Track Thermochronology; Geochrnology; Apatite; Zircon; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS